Aramid coating slurry, diaphragm and preparation method and application thereof

By using a combination of silanized modified inorganic ceramic particles and surfactant, combined with the steam bath pre-solidation process, the heat shrinkage and adhesion of lithium-ion battery separators at high temperatures is solved, and high stability and breathability are achieved The aramid coating extends the battery life and reduces environmental pollution.

CN118943660BActive Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411412036.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have high heat shrinkage at high temperatures, which can easily lead to short circuits and safety accidents. The preparation method of aramid coating uses organic solvents to cause environmental pollution and poor adhesion.

Method used

It is composed of 1-8 wt% aramid, 3-10 wt% cosolvent, 0.3-6 wt% silanized modified inorganic ceramic particles, 0.03-0.6 wt% surfactant and 75.4-95.67 wt% organic solvent. The aramid coating slurry forms a highly stable and breathable coating through uniform dispersion and hydrogen bond interaction of silanized modified inorganic ceramic particles, combined with the steam bath pre-solidation process.

Benefits of technology

It significantly improves the heat resistance and service life of the lithium-ion battery separator, reduces the use of organic solvents, avoids environmental pollution, and maintains the breathability and adhesion of the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118943660B_ABST
    Figure CN118943660B_ABST
Patent Text Reader

Abstract

The present invention discloses an aramid coating slurry, a diaphragm and a preparation method and application thereof, and belongs to the field of battery diaphragms. The aramid coating slurry of the present invention comprises aramid 1‑8wt%, a cosolvent 3-10wt%, silanized modified inorganic ceramic particles 0.3-6wt%, a surfactant 0.03-0.6wt%, and an organic solvent 75.4-95.67wt%. The diaphragm comprises a base film and an aramid coating coated on one side or both sides of the base film. The coating of the present invention has good interfacial adhesion with the base film, and on the basis of not affecting the air permeability of the diaphragm, the heat resistance and electrolyte wettability of the diaphragm are improved, and the safety performance of the lithium ion battery diaphragm is improved. The present invention adopts a steam-induced phase inversion method to form a gel film, reduces the discharge of wastewater, and has the characteristics of being environmentally friendly, simple in process, and convenient for continuous production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aramid coating slurry, a diaphragm and a preparation method and application thereof, and belongs to the field of battery diaphragms. Background Art

[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their high energy density, high operating voltage, no memory effect and long cycle life. However, frequent lithium-ion battery safety accidents have attracted people's attention. Lithium-ion batteries usually include positive electrodes, negative electrodes, separators and electrolytes. As a barrier between the positive and negative electrodes, the separator plays a vital role in the performance of lithium-ion batteries. Therefore, research on improving the safety, usability and processability of lithium-ion batteries by improving the performance of the separator has received more and more attention.

[0003] Polyolefin separators (polyethylene PE, polypropylene PP) are the most widely used lithium-ion battery separators at present, but they have the problem of too high thermal shrinkage, softening and deformation at temperatures above 100°C, and the melting point is lower than 170°C. When the battery temperature rises due to internal or external factors, the separator will shrink or melt and then rupture, causing the positive and negative electrodes of the battery to contact, resulting in a short circuit in the battery, causing accidents such as battery combustion and explosion. In order to improve the thermal stability of polyolefin separators, the current main solution is to coat one or both sides of the polyolefin separator. During the battery charging and discharging process, even if the polyolefin film shrinks or even melts, the coating can still maintain the integrity of the separator, effectively preventing large positive and negative area short circuits, and at the same time, it can effectively improve the surface tension of the separator, reduce the interface impedance between the separator and the pole piece, and improve the liquid absorption performance of the separator. There are currently two commonly used coating materials for diaphragm coatings. One is inorganic coatings, such as alumina, boehmite, silica and other ceramic coatings, which can effectively improve the high-temperature resistance of the diaphragm. However, the ceramic coating has poor bonding with the base membrane and is prone to powdering problems. The addition of binders will cause the diaphragm's air permeability to deteriorate, and the strong water absorption of ceramics will cause the battery performance to deteriorate. The other is PVDF coating, which can effectively improve the adhesion between the diaphragm and the electrode, but has limited improvement in the diaphragm's high-temperature resistance.

[0004] Aramid is the full name of "poly (p-phenylene isophthalamide)", which has excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight. Its thermal decomposition temperature can reach 400-430°C. As a separator coating for lithium-ion batteries, it can greatly improve the heat resistance and safety performance of the battery. However, when preparing aramid coated separators, organic solvents such as DMAC, DMF, NMP, and DMSO are often used in combination with co-solvents to dissolve aramid fibers, and then emulsifiers and adhesives are added to the aramid fiber solution to mix them into slurry, and then inorganic nanoparticles such as alumina and silica are introduced to prepare aramid slurry. After coating, pre-solidification in a coagulation bath, washing and drying, aramid coated lithium-ion battery separators are finally obtained. This method has the following problems: 1. Using organic solvents as coagulation baths causes serious environmental pollution; 2. It is difficult for inorganic nanoparticles to disperse in organic solvents, which affects the uniformity of the coating and pore formation; 3. The addition of emulsifiers and binders increases the time for slurry preparation and increases the air permeability of the coating film; 4. The coating formed by the aramid slurry has poor adhesion to the base film and is easy to fall off. Therefore, how to apply aramid to the lithium-ion battery separator coating liquid to greatly improve the heat resistance stability and heat resistance shrinkage rate of the lithium battery separator, improve battery performance, extend service life, and enhance market competitiveness is a problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide an aramid coating slurry, which is composed of 1-8wt% of aramid, 3~10wt% of a solvent, 0.3~6wt% of silanized modified inorganic ceramic particles, 0.03~0.6wt% of a surfactant, and 75.4~95.67wt% of an organic solvent in terms of mass percentage.

[0006] The second object of the present invention is to provide a method for preparing an aramid coating slurry, the preparation method comprising the following steps:

[0007] 1) Mix 1-5wt% of inorganic ceramic particles, 2-15wt% of silane coupling agent and 80-97wt% of solvent 1, heat to 60-80°C, stir and reflux for 12-36h, wash with ethanol 3-5 times, and dry in an oven at 60-80°C to obtain silanized modified inorganic ceramic particles;

[0008] 2) The silanized modified inorganic ceramic particles obtained in (1), the surfactant and the solvent 2 are uniformly stirred, and sand-milled for 5-15 minutes at room temperature of 20-25° C. to obtain an inorganic ceramic particle dispersion;

[0009] 3) Mix aramid, cosolvent and solvent 3, stir at 80-110°C for 5-12h until aramid is completely dissolved, and cool to room temperature 20-25°C to obtain aramid solution;

[0010] 4) Mix the inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3), and stir at room temperature of 20-25° C. for 1-5 h until the dispersion is uniform, to obtain an aramid coating slurry.

[0011] The silanized modified inorganic ceramic particles in the present application can be quickly dispersed evenly in an organic solvent and are not easy to precipitate. In addition, there is a hydrogen bond interaction between the organic group at the other end of the silane coupling agent and the amide group of the aramid, which significantly improves the stability of the coating. In addition, the surfactant used in the present application can significantly adjust the wettability of the coating liquid to the base film, while improving the coating uniformity and adhesion to the base film, and will not affect the air permeability of the coated diaphragm. More importantly, the silane coupling agent and surfactant used in the present application can interact with the electrolyte, while improving the wettability of the electrolyte, can promote the formation of an in-situ SEI film, thereby significantly extending the service life of the lithium-ion battery.

[0012] Preferably, the inorganic ceramic particles in step (1) are selected from one or more of aluminum oxide, silicon dioxide, zirconium oxide, zinc oxide and barium oxide.

[0013] Preferably, the silane coupling agent in step (1) is selected from one or more of an aminosilane coupling agent, a vinylsilane coupling agent, a mercaptosilane coupling agent, a fluorine-based silane coupling agent, and a carboxyl silane coupling agent.

[0014] Preferably, the aminosilane coupling agent in step (1) includes one or more of KH-910, KH-550, and KH-540; the vinylsilane coupling agent includes YDH-171; the mercaptosilane coupling agent includes one or more of KH590 and KH580; the fluorine-based silane coupling agent includes trichloro(3,3,3-trifluoropropyl)silane; and the carboxyl silane coupling agent includes Silane-PEG-COOH.

[0015] Preferably, the solvent 1 in step (1) is selected from one or more of toluene, ethanol, methanol and water.

[0016] Further preferably, the silane coupling agent in step (1) is one or more of mercaptosilane coupling agent (KH590, KH580) and carboxylsilane coupling agent (Silane-PEG-COOH). Solvent 1 is preferably one or more of toluene and ethanol.

[0017] Appropriate silane coupling agent and solvent 1 can make the silanization degree of inorganic ceramic particles higher, thereby promoting their uniform dispersion in the organic solvent, forming a cross-linked network structure under the hydrogen bond interaction with aramid, thereby improving the mechanical strength and coating stability.

[0018] Preferably, the surfactant is selected from one or more of polyether-modified siloxane, polyether-modified silicone, polyacrylate, fluorocarbon-modified polyacrylate, polyester and perfluorinated surfactants.

[0019] Further preferably, the surfactant is selected from one or more of polyether-modified siloxane, fluorocarbon-modified polyacrylate, and perfluorinated surfactant.

[0020] Preferably, the solvent 2 is selected from at least one of DMAc, NMP, DMF and DMSO.

[0021] Preferably, the solvent 3 is selected from at least one of DMAc, NMP, DMF and DMSO.

[0022] Further preferably, the solvent 2 and the solvent 3 are selected from DMAc and / or NMP.

[0023] DMAC and NMP have better solubility in aramid and better dispersibility in silanized modified inorganic ceramic particles, and can be used to prepare slurry more easily.

[0024] Preferably, the co-solvent is selected from at least one of lithium chloride, calcium chloride, magnesium chloride and sodium chloride.

[0025] During the coating process, appropriate surfactants can effectively adjust the static and dynamic surface tension of the slurry, which can not only promote the diffusion of the slurry into the cortex and surface layer of the base membrane, thereby improving the adhesion with the base membrane, but also make the penetration of the slurry in the base membrane stay only in the cortex and surface layer of the base membrane, without diffusing to the inner layer, thereby not affecting the air permeability of the diaphragm.

[0026] The third purpose of the present application is to provide an aramid coated diaphragm, the diaphragm comprising a base film and an aramid coating coated on one or both sides of the base film, the thickness of the single layer coating being 0.5-4 µm (i.e. the thickness of the coating on each side being 0.5-4 µm). The base film comprises a commercial PP single layer film, a PE single layer film or a PP and PE multi-layer composite base film, the thickness being 5-12 µm. The aramid coated diaphragm is prepared by the following method using the aramid slurry described in one of the purposes:

[0027] 1) applying the aramid coating slurry on one side or both sides of the base film to obtain a coating film;

[0028] 2) The coating film is slowly precipitated in a saturated steam bath, then washed in a water washing tank, and dried in an oven to finally obtain an aramid coated diaphragm.

[0029] Preferably, the coating method in step 1) includes any one of micro-dimple coating, slit coating, dip coating, wire rod coating and blade coating.

[0030] Further preferably, the coating method is micro-dimple coating and / or wire rod coating.

[0031] Preferably, the temperature of the saturated steam bath in step 2) is 40-70° C., the humidity is 50-90% RH, and the coating precipitation time is 5-60 s.

[0032] Further preferably, the temperature of the saturated steam bath is 50-65°C, the humidity is 65-90%RH, and the coating precipitation time is 30-60s, including but not limited to saturated steam bath 50°C, 90%RH, coating precipitation 55s; saturated steam bath 60°C, 90%RH, coating precipitation 30s; saturated steam bath 50°C, 70%RH, coating precipitation 60s, etc.

[0033] Preferably, the water washing tank in step 2) has 3 sections, all of which are filled with pure water, and the washing time of each section is 10-200s.

[0034] More preferably, each water washing time is 50-200s, including but not limited to the first water washing time of 200s, the second water washing time of 100s, and the third water washing time of 50s; the first water washing time of 100s, the second water washing time of 100s, and the third water washing time of 50s; the first water washing time of 200s, the second water washing time of 50s, and the third water washing time of 50s, etc.

[0035] Preferably, the drying oven has two sections, the first section has a drying temperature of 45-55°C and a drying time of 30-100s; the second section has a drying temperature of 50-60°C and a drying time of 30-100s.

[0036] The use of a steam bath instead of a coagulation bath for the pre-coagulation process reduces the amount of organic solvents used and avoids the generation of a large amount of solvent-containing wastewater. At the same time, the high humidity environment of the steam bath makes the coagulation rate of the coating consistent during the pre-coagulation process, thereby avoiding the formation of a dense cortical structure and eventually forming open pores, which improves the wettability of the electrolyte.

[0037] The fourth object of the present application is to provide an application of the above-mentioned aramid coated diaphragm in a lithium ion battery.

[0038] Compared with the prior art, the aramid coated diaphragm provided by the present invention has the following advantages:

[0039] (1) In the present application, silanized inorganic ceramic particles and aramid are used to prepare aramid coating slurry. The silanized inorganic ceramic particles can be quickly dispersed and uniformly dispersed in an organic solvent and are not easy to precipitate. In addition, there is a hydrogen bond interaction between the organic group at the other end of the silane coupling agent and the amide group of the aramid, which significantly improves the stability and mechanical strength of the coating.

[0040] (2) The surfactant used in the present application can significantly adjust the wettability of the coating liquid to the base film, thereby improving the coating uniformity and adhesion to the base film without affecting the air permeability of the coated membrane.

[0041] (3) The silane coupling agent and surfactant used in the present application interact with the electrolyte, and while improving the wettability of the electrolyte, they can promote the formation of an in-situ SEI film, thereby significantly extending the service life of the lithium-ion battery.

[0042] (4) The present application uses a steam bath instead of a coagulation bath for the pre-coagulation process. The high humidity environment of the steam bath makes the coagulation rate of the coating consistent during the pre-coagulation process, thereby avoiding the formation of a dense cortical structure and eventually forming open pores, thereby improving the wettability of the electrolyte. At the same time, the use of organic solvents is reduced, avoiding the generation of a large amount of solvent-containing wastewater, and being environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a surface morphology image of the aramid coated diaphragm in Example 1 of the present invention;

[0044] Figure 2 is a surface morphology diagram of the aramid coated diaphragm in Comparative Example 1 of the present invention;

[0045] Figure 3 1 is a graph showing the battery performance of Example 1 of the present invention and Comparative Examples 1 and 3. DETAILED DESCRIPTION

[0046] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.

[0047] Example 1

[0048] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0049] Preparation of aramid coating slurry: 1) 5 wt% silica, 15 wt% silane coupling agent Silane-PEG-COOH and 80 wt% toluene were mixed, heated to 75°C, stirred and refluxed for 36 hours, washed with ethanol 5 times, and dried in an oven at 80°C to obtain silanized modified silica; 2) 3 g of silanized modified silica obtained in (1), 0.1 g of surfactant polyether modified siloxane, and 30 g of solvent DMAC were mixed evenly, and sanded at room temperature of 25°C for 5 minutes to obtain an inorganic ceramic particle dispersion; 3) 5 g aramid, 5 g of co-solvent lithium chloride, and 56.9 g of solvent DMAC were mixed, stirred at 80°C for 10 hours until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature of 25°C for 1 hour until the dispersion was uniform to obtain an aramid coating slurry.

[0050] Preparation of aramid coated diaphragm: 1) The above aramid coated slurry was coated on one side of a 7µm PE base film through micro-concave coating to obtain a coated membrane; 2) The coated membrane was slowly precipitated with a coating in a saturated steam bath at 60°C and 90%RH for 30 seconds, and then washed with water in 3 water washing tanks for 100 seconds, 100 seconds and 50 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, and finally an aramid coated diaphragm was obtained with a coating thickness of 1.5µm.

[0051] Example 2

[0052] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0053] Preparation of aramid coating slurry: 1) 1 wt% of zirconium oxide, 2 wt% of silane coupling agent KH580 and 97 wt% of methanol were mixed, heated to 80°C, stirred and refluxed for 24 h, washed with ethanol three times, and dried in an oven at 80°C to obtain silanized modified zirconium oxide; 2) 1 g of the silanized modified zirconium oxide obtained in (1), 0.1 g of surfactant polyether-modified silicone, and 10 g of solvent NMP were mixed evenly, and sanded at room temperature of 20°C for 15 min to obtain an inorganic ceramic particle dispersion; 3) 5 g of aramid, 7 g of co-solvent calcium chloride, and 76.9 g of solvent NMP were mixed, stirred at 80°C for 12 h until the aramid was completely dissolved, and cooled to room temperature of 20°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature of 20°C for 2 h until they were evenly dispersed to obtain an aramid coating slurry.

[0054] Preparation of aramid coated diaphragm: 1) The aramid coated slurry is coated on one side of a 5µm PE base film through a wire rod to obtain a coated membrane; 2) The coated membrane is slowly precipitated with a coating in a saturated steam bath at 40°C and 70%RH for 60 seconds, and then washed in 3 water washing tanks for 200 seconds, 200 seconds and 200 seconds respectively, dried in an oven at 55°C for 30 seconds in the first stage, and dried in an oven at 60°C for 30 seconds in the second stage, to finally obtain an aramid coated diaphragm with a coating thickness of 0.5µm.

[0055] Example 3

[0056] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0057] Preparation of aramid coating slurry: 1) 3 wt% of alumina, 5 wt% of silane coupling agent KH590 and 90 wt% of ethanol were mixed, heated to 60°C, stirred and refluxed for 12 h, washed with ethanol 4 times, and dried in an oven at 70°C to obtain silanized modified alumina; 2) 6 g of silanized modified alumina obtained in (1), 0.6 g of surfactant fluorocarbon modified polyacrylate, and 10 g of solvent DMF were mixed evenly, and sanded at room temperature of 25°C for 10 min to obtain an inorganic ceramic particle dispersion; 3) 8 g of aramid, 10 g of co-solvent sodium chloride, and 65.4 g of solvent DMF were mixed, stirred at 110°C for 5 h until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature of 25°C for 5 h until they were evenly dispersed to obtain an aramid coating slurry.

[0058] Preparation of aramid coated diaphragm: 1) The aramid coated slurry was applied to one side of a 12µm PE base film by a scraper to obtain a coated film; 2) The coated film was slowly precipitated with a coating in a saturated steam bath at 70°C and 50% RH for 5 seconds, and then washed with water in 3 water washing tanks for 10 seconds, 100 seconds and 100 seconds respectively, dried in an oven at 45°C for 100 seconds in the first section, and dried in an oven at 55°C for 100 seconds in the second section, and finally an aramid coated diaphragm was obtained with a coating thickness of 1.5µm.

[0059] Example 4

[0060] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0061] Preparation of aramid coating slurry: 1) 5 wt% barium oxide, 10 wt% silane coupling agent KH910 and 85 wt% water are mixed, heated to 80°C, stirred and refluxed for 24 h, washed with ethanol 5 times, and dried in an oven at 60°C to obtain silanized modified barium oxide; 2) 1 g of the silanized modified barium oxide obtained in (1), 0.1 g of surfactant polyacrylate, and 10 g of solvent DMSO are stirred evenly, and sand-milled at room temperature of 25°C for 5 min to obtain an inorganic ceramic particle dispersion; 3) 5 g aramid, 7 g of co-solvent magnesium chloride, and 76.9 g of solvent DMSO are mixed, stirred at 80°C for 10 h until the aramid is completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) are mixed, stirred at room temperature of 25°C for 2 h until uniformly dispersed, to obtain an aramid coating slurry.

[0062] Preparation of aramid coated diaphragm: 1) The aramid coating slurry was dip-coated on both sides of a 7µm PP base film to obtain a coated membrane; 2) The coated membrane was slowly precipitated with a coating in a saturated steam bath at 50°C and 90% RH for 30 seconds, and then washed in 3 water washing tanks for 50 seconds, 100 seconds and 100 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, to finally obtain an aramid coated diaphragm with a coating thickness of 4µm.

[0063] Example 5

[0064] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0065] Preparation of aramid coating slurry: 1) 5 wt% zinc oxide, 5 wt% silane coupling agent YDH-171 and 90 wt% ethanol were mixed, heated to 75°C, stirred and refluxed for 36 hours, washed with ethanol 5 times, and dried in an oven at 80°C to obtain silanized modified zinc oxide; 2) 0.3 g of silanized modified zinc oxide obtained in (1), 0.03 g of perfluoro surfactant and 10 g of solvent DMF were mixed evenly, and sand-milled at room temperature of 25°C for 5 minutes to obtain an inorganic ceramic particle dispersion; 3) 1 g aramid, 3 g of co-solvent lithium chloride and 85.67 g of solvent DMF were mixed, stirred at 80°C for 10 hours until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, stirred at room temperature of 25°C for 2 hours until the dispersion was uniform, and an aramid coating slurry was obtained.

[0066] Preparation of aramid coated diaphragm: 1) Slit-coat the above-mentioned aramid coated slurry on one side of a 7µm PP and PE multilayer composite base film to obtain a coated film; 2) The coated film is slowly precipitated with a coating in a saturated steam bath at 50°C and 90%RH for 30 seconds, and then washed with water in 3 water washing tanks for 50 seconds, 100 seconds and 100 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, to finally obtain an aramid coated diaphragm with a coating thickness of 1.5µm.

[0067] Example 6

[0068] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0069] Preparation of aramid coating slurry: 1) 5 wt% zinc oxide, 5 wt% silane coupling agent trichloro(3,3,3-trifluoropropyl)silane and 90 wt% ethanol were mixed, heated to 75°C, stirred and refluxed for 36 h, washed with ethanol 5 times, and dried in an oven at 80°C to obtain silanized modified zinc oxide; 2) 0.3 g of silanized modified zinc oxide obtained in (1), 0.03 g of polyester surfactant and 10 g of solvent DMF were mixed evenly, and sanded at room temperature of 25°C for 5 min to obtain an inorganic ceramic particle dispersion; 3) 1 g aramid, 3 g of co-solvent lithium chloride and 85.67 g of solvent DMF were mixed, stirred at 80°C for 10 h until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, stirred at room temperature of 25°C for 2 h until uniformly dispersed, to obtain an aramid coating slurry.

[0070] Preparation of aramid coated diaphragm: 1) Slit-coat the above-mentioned aramid coated slurry on one side of a 7µm PP and PE multilayer composite base film to obtain a coated film; 2) The coated film is slowly precipitated with a coating in a saturated steam bath at 50°C and 90%RH for 30 seconds, and then washed with water in 3 water washing tanks for 50 seconds, 100 seconds and 100 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, to finally obtain an aramid coated diaphragm with a coating thickness of 1.5µm.

[0071] Comparative Example 1

[0072] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0073] Preparation of aramid coating slurry: 3g silica, 0.1g surfactant polyether modified siloxane, and 30g solvent DMAC were mixed evenly, and sanded at room temperature 25°C for 5 minutes to obtain an inorganic ceramic particle dispersion; 3) 5g aramid, 5g co-solvent lithium chloride, and 56.9g solvent DMAC were mixed, stirred at 80°C for 10 hours until the aramid was completely dissolved, and cooled to room temperature 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature 25°C for 1 hour until they were evenly dispersed to obtain an aramid coating slurry.

[0074] Preparation of aramid coated diaphragm: 1) The above aramid coated slurry was coated on one side of a 7µm PE base film through micro-concave coating to obtain a coated membrane; 2) The coated membrane was slowly precipitated with a coating in a saturated steam bath at 60°C and 90%RH for 30 seconds, and then washed with water in 3 water washing tanks for 100 seconds, 100 seconds and 50 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, and finally an aramid coated diaphragm was obtained with a coating thickness of 1.5µm.

[0075] Comparative Example 2

[0076] An aramid coating slurry, a diaphragm and a preparation method thereof, comprising the following steps:

[0077] Preparation of aramid coating slurry: 1) 5 wt% silica, 15 wt% silane coupling agent Silane-PEG-COOH and 80 wt% toluene were mixed, heated to 75°C, stirred and refluxed for 36 h, washed with ethanol 5 times, and dried in an oven at 80°C to obtain silanized modified silica; 2) 3 g of silanized modified silica obtained in (1) and 30 g of solvent DMAC were mixed and evenly mixed, and sand-milled at room temperature of 25°C for 5 min to obtain an inorganic ceramic particle dispersion; 3) 5 g aramid, 5 g of co-solvent lithium chloride and 57 g of solvent DMAC were mixed, stirred at 80°C for 10 h until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature of 25°C for 1 h until the dispersion was uniform to obtain an aramid coating slurry.

[0078] Preparation of aramid coated diaphragm: 1) The above aramid coated slurry was coated on one side of a 7µm PE base film through micro-concave coating to obtain a coated membrane; 2) The coated membrane was slowly precipitated with a coating in a saturated steam bath at 60°C and 90%RH for 30 seconds, and then washed with water in 3 water washing tanks for 100 seconds, 100 seconds and 50 seconds respectively, dried in an oven at 50°C for 50 seconds in the first section, and dried in an oven at 50°C for 50 seconds in the second section, and finally an aramid coated diaphragm was obtained with a coating thickness of 1.5µm.

[0079] Comparative Example 3

[0080] The PE base film used in all the above-mentioned Example 1 and Comparative Example 1.

[0081] Comparative Example 4

[0082] Preparation of aramid coating slurry: 1) 5 wt% silica, 15 wt% silane coupling agent Silane-PEG-COOH and 80 wt% toluene were mixed, heated to 75°C, stirred and refluxed for 36 hours, washed with ethanol 5 times, and dried in an oven at 80°C to obtain silanized modified silica; 2) 3 g of silanized modified silica obtained in (1), 0.1 g of surfactant polyether modified siloxane, and 30 g of solvent DMAC were mixed evenly, and sanded at room temperature of 25°C for 5 minutes to obtain an inorganic ceramic particle dispersion; 3) 5 g aramid, 5 g of co-solvent lithium chloride, and 56.9 g of solvent DMAC were mixed, stirred at 80°C for 10 hours until the aramid was completely dissolved, and cooled to room temperature of 25°C to obtain an aramid solution; 4) The inorganic ceramic particle dispersion obtained in step (2) and the aramid solution obtained in step (3) were mixed, and stirred at room temperature of 25°C for 1 hour until the dispersion was uniform to obtain an aramid coating slurry.

[0083] Preparation of aramid coated diaphragm: 1) The aramid coated slurry is coated on one side of a 7µm PE base film through micro-concave coating to obtain a coated membrane; 2) The coated membrane is coagulated in two coagulation baths for 100s and 100s respectively, wherein the first coagulation bath is 35wt% DMAC+65wt% water, and the second coagulation bath is 15wt% DMAC+85wt% water; The pre-coagulated membrane is then washed in two water washing tanks for 100s and 50s respectively; The first section is dried in a 50°C oven for 50s, and the second section is dried in a 50°C oven for 50s, and finally an aramid coated diaphragm is obtained with a coating thickness of 1.5µm.

[0084] Performance Test 1: The aramid coated diaphragms obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for heat shrinkage, coating peel strength, electrolyte absorption rate and air permeability. The specific test methods are as follows. The test results are shown in Table 1.

[0085] Thermal shrinkage rate: Cut the aramid coated diaphragm into 100×100mm film samples, measure their longitudinal and transverse lengths, put them into a vacuum oven and bake them for 1h respectively, take out the diaphragm samples, cool them to room temperature, measure their longitudinal and transverse lengths again, calculate the thermal shrinkage rate, and characterize the heat resistance of the aramid coated diaphragm. Tests were conducted at three temperatures: 105℃, 120℃ and 150℃.

[0086] Coating peel strength: The peel strength is tested using a universal tensile testing machine, and the standard used is "GB / T1040.32-2006 Test for tensile properties of plastics".

[0087] Electrolyte absorption rate: The electrolyte solvent (ethylene carbonate and dimethyl carbonate, with a mass ratio of 1:1) was used as the test object for the absorption rate. The standard adopted was QB / T 2303.11-2008 "Pulp paper for batteries Part 11: Determination of absorption rate", which characterizes the wettability of aramid coated diaphragm to electrolyte.

[0088] Air permeability: The air permeability tester is used to test the air permeability of the aramid coated diaphragm.

[0089] Table 1 Heat shrinkage, peel strength, liquid absorption and air permeability of the aramid coated separators in Examples 1-6 of the present invention and Comparative Examples 1-4

[0090]

[0091] As can be seen from Table 1, the heat resistance of the aramid coated diaphragm provided by Examples 1 to 6 and Comparative Examples 1 to 2 / 4 is much higher than that of Comparative Example 3, indicating that the introduction of the aramid coating significantly increases the thermal stability of the diaphragm. In addition, the peel strength and electrolyte wettability of the aramid coated diaphragm provided by Example 1 are much higher than those of Comparative Examples 1 to 2, indicating that the introduction of the surfactant improves the adhesion between the coating and the base film, and the combined effect of the surfactant and the silane coupling agent improves the wettability of the diaphragm to the electrolyte. In addition, compared with Comparative Example 3, the air permeability of the aramid coated diaphragms of Examples 1 to 6 is not greatly improved, indicating that the surfactant not only promotes the diffusion of the slurry to the cortex and surface layer of the base film, thereby improving the adhesion with the base film, but also enables the penetration of the slurry in the base film to stay only in the cortex and surface layer of the base film, and not to diffuse to the inner layer, thereby not affecting the air permeability of the diaphragm. Compared with Comparative Example 4, the wettability of the electrolyte of the aramid coated diaphragms of Examples 1 to 6 is significantly improved. This is because the present application uses a steam bath instead of a coagulation bath for the pre-coagulation process. The high humidity environment of the steam bath makes the coagulation rate of the coating consistent during the pre-coagulation process, thereby avoiding the formation of a dense cortical structure and eventually forming open pores, thereby improving the wettability of the electrolyte. At the same time, the amount of organic solvent used is reduced, avoiding the generation of a large amount of solvent-containing wastewater, and being environmentally friendly.

[0092] The separators in Example 1, Comparative Example 1 and Comparative Example 3 were cut into 19 mm discs, 811 pole pieces were used for the positive electrode and graphite negative electrode was used for the negative electrode, and the full battery was assembled to test the rate performance. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the rate performance of the composite diaphragm in Example 1 is significantly improved. This is because the composite functional layer components used in this application have good compatibility with the electrolyte, so that the composite diaphragm has an extremely high liquid absorption rate. In addition, the composite functional layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the wettability and liquid retention rate of the electrolyte. At the same time, compared with Comparative Example 1, the diaphragm in Example 1 has better air permeability and better wettability with the electrolyte, so the performance is optimal.

[0093] The above are only some embodiments of the invention, and do not limit the present invention in any form. All raw material ratios, upper and lower limits of working conditions and interval values ​​in the preparation process of the present invention can realize the present invention, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present invention, when using the above technical content to make some changes or modifications to an equivalent embodiment of decorating, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still belongs to the scope of the technical solution of the present invention.

Claims

1. An aramid coated diaphragm, characterized in that: The diaphragm comprises a base film and an aramid coating coated on one side or both sides of the base film, wherein the thickness of the single-layer coating is 0.5-4 µm; the base film comprises a commercial PP single-layer film, a PE single-layer film or a PP and PE multi-layer composite base film, wherein the thickness of the base film is 5-12 µm; The method for preparing an aramid coated diaphragm comprises the following steps: 1) applying the slurry of the aramid coating on one side or both sides of the base film to obtain a coating film; 2) The coating film is slowly precipitated in a saturated steam bath, then washed in a water washing tank, and dried in an oven to finally obtain an aramid coated diaphragm; The slurry of the aramid coating is composed of 1-8wt% of aramid, 3-10wt% of a cosolvent, 0.3-6wt% of silanized modified inorganic ceramic particles, 0.03-0.6wt% of a surfactant, and 75.4-95.67wt% of an organic solvent according to the mass percentage; The surfactant is selected from one or more of polyether-modified siloxane, polyether-modified silicone, polyacrylate, fluorocarbon-modified polyacrylate, polyester and perfluorinated surfactant; The preparation method of the aramid coating slurry comprises the following steps: 1) mixing 1-5wt% of inorganic ceramic particles, 2-15wt% of silane coupling agent and 80-97wt% of solvent 1, heating to 60-80°C, stirring and refluxing for 12-36h, washing with ethanol for 3-5 times, and drying in an oven at 60-80°C to obtain silanized modified inorganic ceramic particles; 2) mixing the silanized modified inorganic ceramic particles obtained in (1), surfactant and solvent 2 uniformly. , sand grind for 5-15 minutes at room temperature 20-25℃ to obtain an inorganic ceramic particle dispersion; 3) mix aramid, cosolvent and solvent 3, stir for 5-12 hours at 80-110℃ until the aramid is completely dissolved, and cool to room temperature 20-25℃ to obtain an aramid solution; 4) mix the inorganic ceramic particle dispersion obtained in step 2) and the aramid solution obtained in step 3), stir for 1-5 hours at room temperature 20-25℃ until uniformly dispersed, and obtain an aramid coating slurry.

2. The aramid coated diaphragm according to claim 1, characterized in that: The inorganic ceramic particles are selected from one or more of aluminum oxide, silicon dioxide, zirconium oxide, zinc oxide, and barium oxide; the silane coupling agent is selected from one or more of aminosilane coupling agent, vinylsilane coupling agent, mercaptosilane coupling agent, fluorine-based silane coupling agent, and carboxylsilane coupling agent; and the solvent 1 is selected from one or more of toluene, ethanol, methanol, and water.

3. The aramid coated diaphragm according to claim 1, characterized in that: The solvent 2 is selected from at least one of DMAc, NMP, DMF and DMSO.

4. The aramid coated diaphragm according to claim 1, characterized in that: The solvent 3 is selected from at least one of DMAc, NMP, DMF and DMSO; the co-solvent is selected from at least one of lithium chloride, calcium chloride, magnesium chloride and sodium chloride.

5. The aramid coated diaphragm according to claim 1, characterized in that: The coating method includes any one of micro-concave coating, slit coating, dip coating, wire rod coating and blade coating.

6. The aramid coated diaphragm according to claim 1, characterized in that: The temperature of the saturated steam bath is 40-70°C, the humidity is 50-90%RH, and the coating precipitation time is 5-60s; the water washing tank has 3 sections, all filled with pure water, and the water washing time of each section is 10-200s; the drying oven has 2 sections, the first section has a drying temperature of 45-55°C, and the time is 30-100s; the second section has a drying temperature of 50-60°C, and the time is 30-100s.

7. Use of the aramid coated diaphragm according to any one of claims 1 to 6 in a lithium ion battery.

Citation Information

Patent Citations

  • Separator for non-aqueous secondary batteries, and non-aqueous secondary battery

    CN111492504A

  • Composite lithium ion battery diaphragm and preparation method thereof, lithium ion battery and electronic product

    CN111969160A

  • Aramid fiber lithium battery diaphragm with low closed pore and high diaphragm rupture and preparation method of aramid fiber lithium battery diaphragm

    CN115275505A

  • Composite diaphragm, electrochemical device, electronic equipment and mobile terminal

    CN115693024A